Fatigue analysis of wire arc additive manufactured (3D printed) components with unmilled surface. (June 2021) - Bartsch, Helen; Kühne, Ronny; Citarelli, Sandro; Schaffrath, Simon; Feldmann, Markus
Abstract: First investigations have been carried out on the characterisation of the as-welded surface roughness of unmilled wire arc additive manufactured (WAAM) components, followed by an experimental determination of the fatigue strength. Subsequently, randomly based finite-element (FE) simulations are carried out to expand the findings. The statistical characteristics of the surface provide the input values for the Monte-Carlo (MC) simulation. Here, the fatigue strengths of single-wire and multiple-wire welded components have been compared applying the effective notch stress concept performing over 2200 simulations. Finally, a fatigue detail classification for surfaces of WAAM components is given following the principles of EN 1993-1-9 [1].